Group Counseling Using Cinema Therapy Techniques to Reduce the Intensity of Social Media Use in High School Students - Yurisna Yurisna; M. Harwansyah P. Sinaga (Universitas Negeri Semarang, 2024)
This research is motivated by the widespread use of social media among students, which influences lifestyle patterns and learning outcomes among students. This research aims to determine whether group counseling using Cinema Therapy techniques can reduce (decrease) the intensity of social media use among students. The research method used was a quantitative quasi-experiment with a non-equivalent control group, pretest-posttest design. This research used two groups, namely the experimental group and the control group with the medium to high category, taken using purposive sampling techniques. Data collection techniques use observation, interviews, and a social media usage intensity scale which includes four measurement aspects, namely Frequency, duration, attention, and appreciation, which were developed based on Andarwati's (2016) construction and also used the Wilcoxon Test with IMB SPSS version 29 statistical applications. Based on the results of the analysis, the application of group counseling using the cinema therapy technique can reduce the intensity of social media use among students. Penelitian ini dilatar belakangi oleh maraknya penggunaan media social bagi kalangan pelajar, sehingga mempengaruhi pola hidup dan hasil belajar pada kalangan pelajar. Penelitian ini bertujuan untuk mengetahui apakah konseling kelompok dengan teknik Cinema Therapy dapat mereduksi (mengurangi) intensitas penggunaan media sosial pada siswa. Metode penelitian yang digunakan kuantitatif quasi experimen dengan desain Non-equivalent control group Design pretest-posttest. Penelitian ini menggunakan 2 kelompok yaitu kelompok eksperimen dan kelompok control dengan kategori sedang hingga tinggi, di ambil menggunakan teknik puposive sampling. Teknik penggumpulan data menggunakan observasi, wawancara dan skala intensitas penggunaan media sosial dengan meliputi 4 aspek pengukuran yaitu Frekuensi, durasi, perhatian, dan penghayatan yang di kembagkan berdasarkan kontruksi andarwati (2016) dan juga menggunakan Uji Wilcoxon dengan apliksi IMB SPSS statistik versi 29. Berdasarkan hasil analisa dapat disimpulkan bahwa penerapan konseling kelompok dengan teknik Cinema Therapy dapat mengurangi intensitas penggunaan media sosial pada siswa.